2020
DOI: 10.1186/s12883-019-1584-z
|View full text |Cite
|
Sign up to set email alerts
|

Experienced pain after stroke: a cross-sectional 5-year follow-up study

Abstract: Background: Stroke is one of the most common cause of disability worldwide. Pain is common in both stroke survivors and in the general population. Consequences of post-stroke pain (PSP) include reduced quality of life and are important to consider. The aim of the current study was to explore the experience of pain 5 years after stroke, and factors associated with the experience of pain. Methods: Inclusion criteria were: First ever stroke, treated at Sahlgrenska University Hospital, Sweden, during an 18 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…The third study [33] also found a significant association between pain and depression on both the DSM-IV (p = 0.081) and GDS (p = 0.009). The fourth study [3] identified higher levels of depression in individuals who reported more frequent pain compared with those reporting less frequent pain using the Risk of Stroke Scale (p < 0.001) this finding was supported by the anxiety/depression subscale of the EQ-5D (p < 0.001). All significant results were rated as moderately low risk of bias; therefore, it is probable that an association exists.…”
Section: Depression and Pain; Quantitative Evidencementioning
confidence: 81%
See 4 more Smart Citations
“…The third study [33] also found a significant association between pain and depression on both the DSM-IV (p = 0.081) and GDS (p = 0.009). The fourth study [3] identified higher levels of depression in individuals who reported more frequent pain compared with those reporting less frequent pain using the Risk of Stroke Scale (p < 0.001) this finding was supported by the anxiety/depression subscale of the EQ-5D (p < 0.001). All significant results were rated as moderately low risk of bias; therefore, it is probable that an association exists.…”
Section: Depression and Pain; Quantitative Evidencementioning
confidence: 81%
“…Further to this, depression was a significant explanatory factor for experiencing pain (Odds Ratio = 8.0). The significant finding by Westerlind et al, [3] was rated to have moderately low risk of bias whilst the significant result from Choi-Kwon et al [25] was rated to have a high risk of bias and the significant findings from Kong et al [28] and Naess et al [31] were rated as moderately high.…”
Section: Depression and Qol; Quantitative Evidencementioning
confidence: 98%
See 3 more Smart Citations